SIMULATION OF ELECTRONIC EQUIPMENT ELEMENTS COOLING IN SOLIDWORKS - Arkady N. SOLOVIEV; Leila V. GLAZUNOVA (Advanced Engineering Research, 2010)
Hand in hand with the  integration increase of the up-to-date radio electronic equipment (REE) there grows substantially its design complexity, which is associated with an increase in the dimension of the problems solved   in the development process. The application of SAD SolidWorks is an effective way to solve this problem. The problem of calculating the parameters of the radiator cooling for continuous operation of one of the elements of REE is solved with the help of this system.